Świat ideowy amerykańskiego neokonserwatyzmu - Bartyzel, Jacek (Dialogi Polityczne, 2022)
The present article presents a complex and ideological-twists-loaded history of American intellectuals environment, mainly of Jewish origin, with Jews having become over the past half century became one of the most influential groups among the power elite of United States. The starting point for most of them was the fascination with Trockist ideology, (however combined with anti-soviet attitude); with the target being point being, on the other hand – the views referred to as “neoconservatism”, which is in fact a combination of some elements of classical political liberalism, the criticism of the overgrowth of “welfare state” and new-leftist “counterculture”, anti-communism launched from demoliberal positions, and in the second generation of this group: not only anti-islamism but also “democratic imperialism”.